Inside Back Cover: Metal–Organic Frameworks Containing Missing‐Linker Defects Leading to High Hydroxide‐Ion Conductivity (Chem. Eur. J. 5/2016). Issue 5 (20th January 2016) - Montoro, Carmen; Ocón, Pilar; Zamora, Félix; Navarro, Jorge A. R.
Abstract : The deliberate introduction of defects on fcu frameworks, based on Ni8 clusters connected by benzenebipyrazolate linkers, after the treatment with KOH/EtOH leading to missing linker defects and metal cluster basification, is responsible for a boosting of the ion conductivity and depletion of activation energy barrier for the mobility of hydroxide ions. It is worth noting that framework hydrophilicity also plays a major role in order to establish water‐mediated proton‐transfer processes from the basic [Ni8 (OH)5 (EtO)] clusters to the hydration water molecules (Grotthuss mechanism). More information can be found in the Full Paper by J. A. R. Navarro et al. onpage 1646 ff.